2010
DOI: 10.1016/j.juro.2010.01.008
|View full text |Cite|
|
Sign up to set email alerts
|

The Inadequacy of Urinary Dipstick and Microscopy as Surrogate Markers of Urinary Tract Infection in Urological Outpatients With Lower Urinary Tract Symptoms Without Acute Frequency and Dysuria

Abstract: Despite official guidelines and widespread use these tests cannot be considered appropriate for diagnosing urinary tract infection in patients with lower urinary tract symptoms, and should be abandoned in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 16 publications
1
74
0
3
Order By: Relevance
“…The urinary dipstick test for nitrite and leukocyte esterase, calibrated to the Kass criterion, has been found to be unreliable (10)(11)(12). We studied dipsticks, microscopic pyuria, and MSU culture in patients with chronic painless lower urinary tract symptoms (LUTS) and discovered significant sensitivity deficiencies affecting all of these tests (7). Our culture data were very similar to the original findings reported by Stamm et al in 1982, showing that the Kass threshold is misleading (9).…”
Section: Cfu MLsupporting
confidence: 72%
See 2 more Smart Citations
“…The urinary dipstick test for nitrite and leukocyte esterase, calibrated to the Kass criterion, has been found to be unreliable (10)(11)(12). We studied dipsticks, microscopic pyuria, and MSU culture in patients with chronic painless lower urinary tract symptoms (LUTS) and discovered significant sensitivity deficiencies affecting all of these tests (7). Our culture data were very similar to the original findings reported by Stamm et al in 1982, showing that the Kass threshold is misleading (9).…”
Section: Cfu MLsupporting
confidence: 72%
“…Pyuria was very infrequent overall (22% [n ϭ 12] of LUTS patients versus 8% [n ϭ 2] of controls, which is not statistically different [ 2 ϭ 2.4, P ϭ 0.1]). This infrequency is not surprising, considering how weak this marker is for low-grade infections (7,32). Routine culture revealed that very few patients in either cohort tested positive by the Kass criterion (7% [n ϭ 4] of LUTS patients and 11% [n ϭ 3] of controls, which is not statistically different [ 2 ϭ 0.4, P ϭ 0.4]).…”
Section: Spectrum Of Lutsmentioning
confidence: 93%
See 1 more Smart Citation
“…There is a limited evidence, yet general expert consensus that the beneits outweigh the costs [30]. The value of urinary dipstick/microscopy for diagnosing UTI in men with LUTS without acute frequency and dysuria has recently been questioned [31].…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Aşırı antibiyotik kullanımının antibiyotik direncinde artışa sebep olması nedeniyle, sık karşılaşılan ve önemli bir sorun olan ÜSİ'ye doğru tanı konulması önem arz etmektedir (6). Hızlı ve doğru ÜSİ tanısı koyabilmek için laboratuvarlarda çeşitli yöntemlerin etkinliği araştırılmaktadır (7)(8)(9).…”
Section: Introductionunclassified